Dinamika Pelaksanaan Desentralisasi Birokrasi Pelayanan Kesehatan - Ambar Widaningrum (Jurnal Ilmu Sosial dan Ilmu Politik, 2007)
Decentralization represents a good opportunity to improve health services. Specifically, decentralization and related steps can lead to conditions in which district institutions have many discretionary authorities and choices to offer high quality services, and people have the information, financial means, and bargaining power required to elicit appropriate responses. Howeaer, the overall impacts of decentralization on health service depends on its design and institutional arrangements. These need to be supported by appropriate policy instruments and mechanisms.